BIM in the Center of Digital Transformation of the Construction Sector—The Status of BIM Adoption in North Macedonia - Stojanovska-Georgievska, L; Sandeva, I; Krleski, A; Spasevska, H; Ginovska, M; Panchevski, I; Ivanov, R; Perez Arnal, I; Cerovsek, T; Funtik, T (MDPI, 2022)
The building sector nowadays has come to the stage where it needs a “digital” renovation. This is to be accomplished by an introduction of change into the methodology of construction and using new tools and technologies, such as BIM technology. This paper gives an insight into the status of BIM adoption in North Macedonia. It presents the threefold actions toward introduction of BIM in the national construction industry. These actions refer to scanning the current situation regarding digitalization of the sector, then taking promotional actions to express the benefits of BIM, and finally identifying and proposing the most suitable measures, summarized in the proposal of the National Roadmap for BIM adoption. The methods used consist of a brief literature review of the global status of BIM development. Then, the results of a survey conducted on more than 300 respondents representing a sample of building professionals in the country are discussed, and the barriers for successful BIM adoption are accordingly identified. The next step is to showcase the potential benefits of BIM for assessment of energy performance of buildings. As a final point, the conclusions drafted toward identification of the most important challenges are addressed in the proposed National Roadmap for BIM adoption.
Keywords: digitalization; BIM technology; energy performance